Ceramic coatings for orthopaedic implants: preparation and characterization. (22nd December 2015) - Kaciulis, S.; Mezzi, A.; Bianchi, M.; Gambardella, A.; Boi, M.; Liscio, F.; Marcacci, M.; Russo, A.
Abstract : Ceramic coatings are increasingly used for orthopaedic implants to improve the wear resistance and to enhance the integration into bone tissue, resulting in the long‐term stability of the implant. The innovative pulsed plasma deposition technique was used to deposit at room temperature different thin films with required mechanical parameters and good adhesion to the substrate. In this way, the films of nanostructured hydroxyapatite, magnetic hydroxyapatite, zirconia and zirconia ‐ alumina were produced and investigated by X‐ray diffraction, atomic force microscopy and XPS depth profiling techniques. Obtained results revealed the good stoichiometry, sufficient purity of chemical composition, very high uniformity in depth and thermal stability in ultra‐high vacuum of all investigated coatings. Copyright © 2015 John Wiley & Sons, Ltd.